Prophet Isa (AS) and the Miracle of the Feast - "Khan, Saniyasnain" (China; Goodword Books, 2024)
Prophet Isa and the Miracle of the Feast is a beautifully illustrated board book that gently introduces young children to the miraculous story of Prophet Isa (peace be upon him) praying for a heavenly feast. Told in simple, clear language, the story highlights faith, gratitude, and the importance of trusting Allah$1 (Bs mercy. With vibrant, colorful illustrations and sturdy pages, this book is perfect for toddlers and preschoolers. It$1 (Bs an engaging and meaningful way for families to share one of the beloved Quranic stories, encouraging early spiritual growth and understanding.s
Keywords: Prophets stories